Prevalence of Plasmid-mediated Quinolone Resistance (PMQR) Genes and Beta-lactamase Genes among Salmonella, Vibrio parahaemolyticus and Escherichia coli from Shellfish - Divya, Sukumaran P.; Chandradasan, Athira; Pranav, P. K.; Antony, Ally C.; Mohamed Hatha, A. A. (Fishery Technology, 2020)
The objectives of the present study were toinvestigate the prevalence of plasmid-mediatedquinolone-resistance (PMQR) genes and betalactamasegenes in Salmonella, Vibrio parahaemolyticusand Escherichia coli from shellfish. A total of 35Salmonella, 22 Vibrio parahaemolyticus, and 58 Escherichiacoli of shellfish origin were used in this study.Antibiotic susceptibility testing of Salmonella, V.parahaemolyticus, and E. coli against different antibioticswas determined by disc diffusion method. Theminimum inhibitory concentrations (MIC) of nalidixicacid and ciprofloxacin were analyzed bymicrodilution method for all nalidixic acid/ciprofloxacin-resistant strains. All the isolates werescreened for the presence of PMQR genes (qnrA,qnrB, qnrS, qepA, aac(6’)-Ib-cr, and oqxA) and betalactamasegenes (blaTEM, blaSHV, and blaCTXM-1). Theprevalence of nalidixic acid resistance was 5.7, 9,and 3.4% in Salmonella, V. parahaemolyticus and E.coli, respectively. Approximately, 4.5% of V.parahaemolyticus isolates were resistant tociprofloxacin. The prevalence of PMQR harboringSalmonella, V. parahaemolyticus, and E. coli was 22, 9and 3% respectively. The prevalence of betalactamasegenes in Salmonella, V. parahaemolyticus,and E. coli were 17.14, 9 and 5.1%, respectively. The most prevalent PMQR and beta-lactamase genes were qnrS and blaTEM, respectively. The co-occurrence of PMQR and beta-lactamase genes in V. parahaemolyticus and Salmonella, from shellfish, poses a public health concern.